Kajian Yuridis Perlindungan Konsumen Terhadap Pemasaran Produk Perawatan Badan Overclaim di Marketplace - Siska Sari Surya Dewi, Putri; Budi Setianingrum, Reni (Adagium: Jurnal Ilmiah Hukum, 2025)
The rapid growth of Indonesia's body care industry is accompanied by the increasing practice of exaggerated marketing claims (overclaim) on online marketplaces. Such practices can harm consumers’ health and finances due to misleading information without sufficient scientific evidence. This study analyzes legal protection for consumers harmed by overclaim marketing based on Law Number 8 of 1999 on Consumer Protection, Law Number 1 of 2024 on Electronic Information and Transactions, and Law Number 36 of 2009 on Health. Using a normative legal method with a qualitative approach, the study finds that overclaim practices violate consumer rights and may incur administrative or criminal sanctions. However, enforcement in the digital sphere faces challenges such as weak supervision, low consumer awareness, and unclear marketplace responsibilities. Thus, synergy among the government, BPOM, marketplaces, and the public is essential to ensure comprehensive and effective consumer protection in the digital era.